The therapeutic effect of capsaicin on oropharyngeal dysphagia: A systematic review and meta-analysis - Yang, Cong-wen; Chen, Ru-dong; Feng, Meng-ting; Zhang, Meng-zhen; Liu, Wei; Liu, Xu-chang; Wang, Da-chuan (Frontiers in Aging Neuroscience, 2022)
Abstract: Objectives: Capsaicin is a specific agonist of TRPV1(multimodal sensory receptor), which improves oropharyngeal dysphagia by increasing sensory input from the oropharynx and hypopharynx and by increasing repetitive stimulation of the cerebral cortex. The aim of this systematic review was to evaluate the therapeutic effect of capsaicin on swallowing disorders in stroke patients and the elderly. Method: We searched Medline, Embase, PubMed, and Cochrane Library databases. We used the Mesh terms search database to screen all clinical trials that complied with the inclusion criteria. Studies were subjected to literature screening, quality assessment, and data extraction to remove studies that did not meet the inclusion criteria. After literature screening, quality assessment, and data extraction, a systematic review and meta-analysis of the included study were performed. Results: This systematic review and meta-analysis were prospectively registered on PROSPERO under registration number CRD42022320884. Five high-quality randomized controlled trials were ultimately included. The results of our meta-analysis showed a more significant reduction in swallowing function score change in the capsaicin group compared to the control group (SMD=-1.30, 95%CI: [-2.35, -0.25], P=0.01 ). and on the Water swallowing test the improvement was significantly higher in the capsaicin group (RR=2.46, 95%CI: [1.73, 3.50], P<0.0001). Conclusions: Although the results of our meta-analysis showed that capsaicin improved swallowing function, most studies had an unclear bias and included few studies. More studies are needed to support this in the future.